Tip-dating and homoplasy: reconciling the shallow molecular divergences of modern gharials with their long fossil record. Issue 1881 (27th June 2018) - Lee, Michael S. Y.; Yates, Adam M.
Abstract : Simultaneously analysing morphological, molecular and stratigraphic data suggests a potential resolution to a major remaining inconsistency in crocodylian evolution. The ancient, long-snouted thoracosaurs have always been placed near the Indian gharial Gavialis, but their antiquity ( ca 72 Ma) is highly incongruous with genomic evidence for the young age of the Gavialis lineage ( ca 40 Ma). We reconcile this contradiction with an updated morphological dataset and novel analysis, and demonstrate that thoracosaurs are an ancient iteration of long-snouted stem crocodylians unrelated to modern gharials. The extensive similarities between thoracosaurs and Gavialis are shown to be an almost 'perfect storm' of homoplasy, combining convergent adaptions to fish-eating, as well resemblances between genuinely primitive traits (thoracosaurs) and atavisms ( Gavialis ). Phylogenetic methods that ignore stratigraphy (parsimony and undated Bayesian methods) are unable to tease apart these similarities and invariably unite thoracosaurs and Gavialis. However, tip-dated Bayesian approaches additionally consider the large temporal gap separating ancient (thoracosaurs) and modern ( Gavialis ) iterations of similar long-snouted crocodyliforms. These analyses robustly favour a phylogeny which places thoracosaurs basal to crocodylians, far removed from modern gharials, which accordingly are a very young radiation. This phylogenetic uncoupling of ancient and modern gharial-like crocs is more consistent with molecular clock divergence estimates, and also the bulk of the crocodylian fossil record (e.g. all unequivocal gharial fossils are very young). Provided that the priors and models attribute appropriate relative weights to the morphological and stratigraphic signals—an issue that requires investigation—tip-dating approaches are potentially better able to detect homoplasy and improve inferences about phylogenetic relationships, character evolution and divergence dates.